IMPACT OF HYBRID RICE AND MAIZE SEED IN CEREAL PRODUCTION SYSTEM IN BANGLADESH - Anwar, M.M.; Awal, M.A.; Khan, A.S.M. M.R.; Haque, M.E.; Hossain, A. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
The study was undertaken on production and marketing scenario, farmersâ perception and efficiency of hybrid rice and maize producers in Bangladesh. Data from400 farmers and 40 seed dealerswere collected fromDinajpur, Sherpur, Gopalganj andNoakhali district.Ten leading seed companies were also included in the study. About 4 thousand tons of hybrid rice seed were imported by leading 10 seed companies in 2014-15 which was about 38% of total import of hybrid rice seed. BADC is the main hybrid seed producer (HL 8 h) in Bangladesh but it is not more than 10% of total import. Twelve to twenty seven hybrid rice varieties were found in the study districts, and the highest area covered by hybrid in GopalganjSadar (13813 ha) followed by Sonaimuri (7200 ha) ofNoakhali. Farmerâs gross return and gross margin increased by using hybrid rice seed. The solution of the linear programming model shows that area under HYV rice have been shifted to hybrid rice about 8 to 52 percent. The results of stochastic frontier production modelindicated that inefficiency effects are present in hybrid rice and maize production. Hence, technical inefficiency effects have significant impact on output. These results suggest that there is a substantial scope for increasing rice production in the country using hybrid seed. Farmers are happy by producing hybrid rice as it is higher yielder.